Optimalisasi Program Cashless Society di Kota Semarang Berdasarkan Kemitraan antara Pemerintah Kota Semarang dan BNI 46 Regional Kota Semarang dalam Wujud Kartu Semarang Hebat Tahun 2019 - Dwiani Bramastiti; Teguh Yuwono (Journal of Politic and Government Studies, 2020)
Semarang Hebat Card is a new breakthrough from the City of Semarang which aims to advance the concept of smart city as well as the concept of cashless society. In addition, the Great Semarang Card was created to improve public services to the public in different forms or fields. This is a manifestation of government innovation. This Great Semarang Card is expected to have a good impact for the optimization of public services in the city of Semarang.The research method in this thesis uses a mix-method study and descriptive approach. The author takes a research site in Semarang City with a research informant from the government (Diskominfo as a correspondence) and BNI 46 regional Semarang City (Karangayu Branch as a correspondence). The author uses data validation techniques using data triangulation techniques.Great Semarang card is a form of innovation from the concept of cashless society which is applied to cities that are or are in the process of moving towards the concept of smart city. The Great Semarang Card was created from a partnership between the Semarang City Government and BNI 46. BNI 46 was chosen based on its ability to manage smart cards as well as BNI 46 was the chairman of the HIMBARA (State Owned Bank Association). This program has been running from 2017 in 2019, meaning that the Great Semarang Card is two (2) years old. This partnership is conducive with each actor having a duty and role in this program. As a result the Great Semarang Card has an impact on society in many forms or fields. There are fields of mobilization, transactions, and debit cards. The response from the community looked very good as evidenced by the results of the questionnaire. In addition to the response, the community was also affected by his thoughts on applying the concept of cashless in his daily activities. KEYWORDSSemarang City Government, Cashless Society, Smart City, BNI 46